Illegal Annexation and State Continuity The Case of the Incorporation of the Baltic States by the USSR. Second Revised Edition - Mälksoo, Lauri (Brill, 2022)
This volume, now in its second and revised edition, deals with the legal status of the three Baltic States - Estonia, Latvia and Lithuania - as a consequence of the illegality of the Soviet annexation in 1940-1991. It offers a detailed historical overview of the Soviet takeover of the Baltic States in 1939/1940 and analysis of international law as it was in force, also regionally and bilaterally, at the time. It examines the role of the continuity of the diplomatic representations of the Baltic States and other manifestations of the Western non-recognition of the Soviet annexation. Moreover, the book examines the nature of the restoration of the Baltic States in 1991 based on their State continuity claim. It also studies in detail questions such as borders, citizenship and reparation claims, and asks to what extent State continuity could or could not be restored in practice. Compared to the first edition, the text has been updated (for example, on developments regarding border treaties) but also more background references have been added on the history of the Baltic States, Soviet and post-Soviet Russian responses to the continuity claim of the Baltic States, etc. The book interprets the Soviet annexation and Baltic States' continuity case against the wider backdrop of developments in international law in the 20th century and argues that the outcome reflected important normative developments in international law, away from mere effectivity. The case of the Baltic States will be relevant for current and future cases of illegal annexation, following the threat and use of military force prohibited under international law.